Pelatihan Baby Gym sebagai Upaya Meningkatkan Kesadaran Kesehatan Bayi bagi Orang Tua - Susmita Susmita; Tri Sartika (Institut Teknologi dan Bisnis Semarang, 2024)
Around 5-10% of children in the world experience motor development disorders that can indirectly contribute to increasing morbidity rates in a country. Efforts that can be made to overcome motor development disorders are the implementation of baby gym. However, not many parents know the importance of baby gym and how to do it properly. This baby gym training activity is intended to increase parental awareness of infant health and motor development. The activity method is divided into preparation stages, parent socialization, baby gym practical training, mentoring and evaluation. The results obtained are an increase in parental knowledge about the importance of baby gym, an increase in parental skills in doing baby gym and an increase in infant motor development. This baby gym training has a positive impact on increasing parental awareness and skills in supporting infant health and motor development.